Density functional theory based comparative study of electronic structures and magnetic properties of spinel ACr2O4 (A = Mn, Fe, Co, Ni) compounds. (30th September 2015) - Das, Debashish; Ghosh, Subhradip
Abstract: Using the DFT+U method and generalized gradient approximation (GGA) we perform the first systematic study of the chromite series ACr2 O4 (A  =  Mn, Fe, Co, Ni) by computing their structural and magnetic properties. The results are analyzed by their electronic structures. We find that in spite of varying structural distortions, the electronic structures are very similar across the series. Such similarities are responsible for qualitative uniformities in their magnetic phases at low temperatures, as observed in the experiments. We find that the strong electron–electron correlation, along with competing magnetic exchange splitting and the crystal field splitting, are responsible for their electronic properties such as the electronic band gaps. Our results regarding the magnetic exchange parameters are in good agreement with the available results and show the relative importance of the pairwise exchange interactions in each of the compounds. The ground state magnetic spin structures and the ferrimagnetic transition temperatures obtained from these exchange parameters, in combination with a phenomenological theory, qualitatively agree with the experiments and other theoretical results.